Legal Protection of Occupational Health and Safety (K3) Daily Labor from Rice Milling Factory in Indramayu - Santoso, Asep (KnE Social Sciences, 2023)
The relationship between workers and employers involves personal rights and obligations in social life. To ensure the safety of casual daily workers during their work and to achieve optimal work productivity, rice mill entrepreneurs are obligated to comply with the laws and regulations and take measures to prevent work accidents. The purpose of this research is twofold: 1. To identify the legal protection for the occupational safety and health of casual daily workers in rice mills. 2. To determine the legal responsibilities of rice mill entrepreneurs in implementing occupational safety and health measures. The research method used in this study is a juridical-normative research method with a descriptive approach. Legal protection for Occupational Health and Safety is governed by various legislation, including Law Number 1 of 1970 concerning Occupational Safety, Law Number 13 of 2003 concerning Manpower, which provides legal protection for workers’ rights, wages, and welfare. Additionally, there are Government Regulations, Ministerial Regulations, Ministerial Decrees, and Instructions related to Occupational Safety and Health (K3), as well as Circulars and Decrees issued by the Director General of Industrial Relations and Labor Inspection. Keywords: legal protection, occupational health and safety, workers